Diagnostic role of hair magnesium in migraine patients: higher than serum magnesium? - Ilhan, A; Uz, E; Var, A; Kali, S; Akyol, O (Dustri-Verlag Dr Karl Feistle, 2000)
The present study was aimed at evaluating trace element changes and diagnostic role of magnesium levels in hair of migraine patients during interictal period. We assessed trace element levels in hair of migraine patients (n = 40) and control subjects (n = 21). In the group of migraineurs,magnesium (p < 0.05), zinc (p < 0.05), and copper (p < 0.001) levels in the hair were significantly reduced with regard to the control subjects. Although the hair levels of manganese and serum levels of magnesium are lower in migraine patients than the levels in controls, these differences were not found to be signifcant. Also, the mean trace element levels in the group of migraine patients showed no significant difference according to gender, age, and type of migraine (with or without aura). Our data show that some hair trace element levels change in migraine patients during interictal period and hair magnesium seems to be more valuable than serum magnesium as a diagnostic marker in migraine.
Keywords: migraine; hair; magnesium; trace element